Penerapan Teknologi irigasi Tetes Pada Agrowista Anggur - Refranisa, Refranisa; Rochimah, Estuti; Apriliasi, Eka (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2023)
Keranggan Village has a large area of land for agrotourism development, with the main attraction as an Ecotourism Village. Pokdarwis members, as partners in community service, have joined the South Tangerang Grape Community. They highlight grapes as the village's leading commodity to support its Ecotourism Village title. However, several aspects of the problems faced by Pokdarwis are aspects of agrotourism plant cultivation techniques and aspects of human resource management in applying agrotourism plant cultivation technology. The service aims to introduce grape cultivation technology and increase knowledge of grape cultivation techniques using drip irrigation techniques. Several solutions are offered to partners: (1) pioneering grape cultivation by the community, which can be used as a fruit-picking attraction; (2) applying digital drip irrigation techniques as irrigation support to support grape plant productivity; and (3) providing training and assistance to the community so that they have the skills to implement grape cultivation and apply drip irrigation technology. The results and implications of this program are that the people of Keranggan village can apply suitable technology that makes it easier to grow grapes and makes Keranggan village a pioneer of grape agrotourism in South Tangerang.